Peningkatan Nilai Tambah Kakao Lokal Desa Pahawang melalui Pelatihan Produksi Sabun Kakao - Sari, Dian Anggria; Istiadi, Khaerunissa Anbar; Suryanti, Erma; Chusniasih, Dewi; Imaniar, Lisana Husna; Ningsih, Ningsih (LPMP Imperium, 2026)
Pahawang Village is an island with strong marine tourism potential in Lampung. In addition to working as fishermen, many villagers also cultivate cocoa as an agricultural commodity. To date, cocoa beans have only been sold in dried form and have not been processed into other value-added products. In order to increase value added and support the village’s creative economy, product innovations derived from cocoa with high market value and simple production technology are needed. Cocoa beans contain active compounds such as catechins, anthocyanins, and natural fats that function as antioxidants and skin moisturizers. The purpose of this activity was to increase the value of cocoa by processing it into economically valuable soap. The method involved socialization and hands-on practice on cocoa soap production. The results showed a significant increase in community knowledge, reaching 92.8%, regarding the production and packaging of creative cocoa-based products. The activity of processing cocoa into soap had a positive impact on the people of Pahawang Village. With the new skills acquired, the community is expected to be able to independently develop cocoa-based home industries, thereby increasing income and economic welfare. The cocoa soap products also have the potential to become a flagship village product that supports nature tourism in Pahawang Village through the provision of souvenirs.